Penerapan Psikologi Pendidikan Agama Kristen dalam Meningkatkan Perkembangan Rohani Anak - Wilson Simanjuntak; Desy H. Sihombing; Edelwis Pardosi; Putra Jungjungan Rajagukguk; Rahel Dwi Ivanna; Hesty Sinaga; Rainaldi Setiawan (Pusat Riset dan Inovasi Nasional, 2025)
Particularly in the context of Christian Religious Education, the question of children's spiritual growth and development is a critical component in the process of character formation, resulting in a holistic personality. Children benefit greatly from the use of Christian Religious Education psychology since it helps them comprehend the importance of faith, morality, and spirituality in a way that is suitable for their stage of psychological development. Data for this study were gathered by analyzing a variety of pertinent literature sources that were linked to the research issue. The author used a qualitative method in conjunction with a library research methodology. The purpose of this study is to examine how Christian Religious Education psychology concepts might be applied to improve children's spiritual development in the smallest social settings the family, school, and church.The study's end findings show that using Christian Religious Education psychology helps kids become more aware of the principles of their faith, behave in ways that emphasize love, behave responsibly, and have a positive relationship with God. It is anticipated that this study will improve the analytical abilities of church ministers, particularly those who specialize in children's ministry, parents of children, and educators who use it as a teaching tool. It is acceptable and effective for the demands of children's spiritual growth and development when a mature and proper technique is used.